Dielectric Function of 2D Tungsten Disulfide in Homo‐ and Heterobilayer Stacking. Issue 3 (1st December 2022) - Peci, Ermes; Magnozzi, Michele; Ramó, Lorenzo; Ferrera, Marzia; Convertino, Domenica; Pace, Simona; Orlandini, Giorgio; Sharma, Apoorva; Milekhin, Ilya; Salvan, Georgeta; Coletti, Camilla; Zahn, Dietrich R. T.; et al.
Abstract: The opto‐electronic properties of semiconducting 2D materials can be flexibly manipulated by engineering the atomic‐scale environment. This can be done by including 2D materials in tailored van der Waals (vdW) stacks, whose optical response is a function of the number and the type of adjacent 2D layers. This work reports a systematic investigation of the dielectric function of 2D semiconducting WS2 in various stacking configurations: monolayer, 3R/2H homobilayer, and WS2 /MoS2 heterobilayer. Reliable, Kramers–Kronig‐consistent dielectric functions are obtained for WS2 in each configuration by means of spectroscopic ellipsometry (SE) and related parametric optical modeling in a wide spectral range (1.55–3.10 eV). The results of SE are combined with photoluminescence and absorbance spectra to identify the spectral position of the main excitonic features in WS2, which manifest sizable redshifts depending on the stacking configuration. These results represent a consistent reference set for the dielectric function of WS2 in vdW stacking configurations of particular interest for the scientific and technological field, and can be fruitfully exploited for reliable predictions of the optical response of WS2 ‐containing systems. Abstract : The opto‐electronic properties of 2D WS2 can be manipulated via its inclusion in van der Waals heterostacks. This spectroscopic ellipsometry investigation highlights the tunability of the excitonic features and provides a set of reference values for the dielectric function of WS2 in monolayer configuration, 2H and 3R bilayer stacking, and WS2 /MoS2 vertical heterostructure.